Enlightenment and its Impact To Vina Convention on The Law of Treaties 1969 - Nadiya Salsabila (Magister Kenotariatan Universitas Pasundan, 2024)
The Enlightenment, particularly the philosophy of Immanuel Kant, profoundly influenced the development of modern international law, including the Vienna Convention on the Law of Treaties (VCLT) 1969. This paper explores the connection between Enlightenment ideals and critical principles in the VCLT, such as pacta sunt servanda (Article 26) and the obligation to respect treaties regardless of internal laws (Article 27). The Enlightenment's emphasis on reason, autonomy, and universal moral obligations is a cornerstone for these principles, ensuring rationality and good faith in international relations. The problem addressed in this study is the extent to which these Enlightenment principles influenced the codification of international treaty law in the VCLT, particularly its emphasis on the binding nature of treaties and the universality of legal obligations. The methodology involves a philosophical and legal analysis of the VCLT's Articles 26 and 27, tracing their conceptual roots to Kantian philosophy and Enlightenment thought. Through this analysis, the findings reveal a direct connection between Enlightenment ideals and the VCLT's principles. Article 26's emphasis on good faith and binding commitments mirrors Kant's views on moral autonomy and universal laws. Article 27 reflects the Enlightenment's belief in universal obligations superseding localized, subjective rules, ensuring the supremacy of reason and international stability. The findings reveal that the VCLT's codification of pacta sunt servanda and related principles embodies the enduring influence of Enlightenment ideals, particularly those of Kant, in shaping a rational, cooperative, and just international legal order.